The New Porcine Epidemic Diarrhea Virus Outbreak May Mean That Existing Commercial Vaccines Are Not Enough to Fully Protect Against the Epidemic Strains - Gao, Qi; Zheng, Zezhong; Wang, Heng; Yi, Songqiang; Zhang, Guihong; Gong, Lang (Frontiers in Veterinary Science, 2021)
Background On October 30, 2020, piglets and sows in the farrowing house of a pig farm in Jiangxi showed clinical symptoms such as anorexia, watery diarrhea, and vomiting. Epidemiological test, clinical necropsy, and RT-PCR test were carried out on the pig farm for diagnosis. After comprehensive considerations, the disease was judged as porcine epidemic diarrhea virus infection. Results Thereafter, a series of comprehensive prevention and control measures such as emergency vaccination with autogenous vaccines were adopted. Half a month after inoculation with autogenous vaccines for the farm, the mortality rate of newborn piglets in the farrowing house began to decline, and production gradually returned to being stable. The second-generation sequencing analysis and phylogenetic analysis showed that the porcine epidemic diarrhea virus (PEDV) sequence obtained from the stool and small intestine samples of the diseased pigs on the farm was 97.8% homologous to the vaccine strain. At the same time, antibody testing found that the vaccinated pigs on the pig farm had satisfactory immune response. Conclusion This case indicating that the PEDV outbreak on the pig farm might aggravate owing to the strain being mutated and could escape the immune protection of the existing vaccine. This case has accumulated technical data for the clinical prevention and control of porcine epidemic diarrhea.